2019
DOI: 10.35381/r.k.v4i8.485
|View full text |Cite
|
Sign up to set email alerts
|

Monitoreo del proceso fermentativo de cuatro licores de frutas (Passiflora edulis, Citrus cinensis, Citrus nobilis y Citrus máxima)

Abstract: Recibido: 23 de mayo de 2019Aprobado: 12 de junio de 2019Esta investigación fue realizada en los laboratorios de la Universidad Técnica de Manabí (UTM) extensión Chone, con el objetivo de monitorear el proceso de fermentación alcohólica de cuatro licores de frutas (maracuyá Passiflora edulis; Naranja Citrus cinensis; mandarina -Citrus nobilis; y Citrus máxima) elaborados artesanalmente. Los parámetros evaluados están regidos en normativas europeas para los vinos y contemplan parámetros como el pH, Azúcar, grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…These values are similar to those obtained by Rodrí guez-Villacis and Herná ndez-Monzón [50], which was 1.024. The study by Arteaga Solórzano et al [51] showed density values between 1.041-1.098 because when sugar is converted into alcohol, the density value decreases. These values are quite similar to those obtained in this research.…”
Section: Densitymentioning
confidence: 99%
“…These values are similar to those obtained by Rodrí guez-Villacis and Herná ndez-Monzón [50], which was 1.024. The study by Arteaga Solórzano et al [51] showed density values between 1.041-1.098 because when sugar is converted into alcohol, the density value decreases. These values are quite similar to those obtained in this research.…”
Section: Densitymentioning
confidence: 99%